Pembelajaran Internal dalam Mendukung Kesuksesan Wirausaha Perempuan - Maretha Ika Prajawati (IKIP PGRI Bojonegoro, 2021)
Entrepreneurial women are those who run a business innovatively, they are also very confident, creative and able to achieve economic independence both individually and collectively with others and increase their active role in economic activities. Entrepreneurship that exists within individuals arises from objective realities that exist in society, which will continue to develop and interact and acculturate so that it will create a new identity for the person concerned so that this raises questions and needs to be studied more deeply about the process of significance in the process. the lessons that women entrepreneurs take towards their business success. This research was conducted in an effort to comprehensively reveal the existence of women entrepreneurs in their activities by using a qualitative approach in order to obtain deeper results. The way in which women entrepreneurs experience the learning process is found in terms of internal locus of control. Learning is important in entrepreneurship, because entrepreneurship reflects the complex interactions between individuals and business situations that are always changing.